Prosedur Pembiayaan Murabahah pada Koperasi Simpan Pinjam Pembiayaan Syariah (KSPP) Al Anshari Bukittinggi - Sari, Chitra Indah; Sulendri, Nia (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2020)
This study aims to determine the procedure for granting Murabahah financing used by the Al-Anshari Bukittinggi Syariah Savings and Loan Cooperative (KSPP). Data collection techniques using observation, interviews, and library research using qualitative descriptive methods. The results of this study indicate that the procedure for granting Murabahah financing implemented by the Al-Anshari Bukittinggi Syariah Savings and Loan Cooperative (KSPP) can run optimally and in accordance with the planned objectives, especially to encourage the efficiency of financing. The efforts made by KJKS BMT Agam Madani Nagari Batu Palano Agam Regency to keep the financing provided smooth, productive and non-performing is to comply with every management policy in providing financing.